Characterization of short- and medium-chain chlorinated paraffins in cereals and legumes from 19 Chinese provinces. (July 2019) - Wang, Runhua; Gao, Lirong; Zheng, Minghui; Li, Jingguang; Zhang, Lei; Wu, Yongning; Wang, Guoquan; Xiong, Lipei; Ding, Danting; Lu, Dasheng; Qiao, Lin; Cui, Lili; et al.
Abstract: Short-chain chlorinated paraffins (SCCPs) were added to the Stockholm Convention Annex A in May 2017. China is the largest producer of chlorinated paraffins (CPs). CPs in the environment can be transferred to foodstuffs directly and through bioaccumulation and then ingested by humans. Cereals and legumes are important components of Chinese diets, so the risks posed by CPs in cereals and legumes should be of concern. 1710 cereal samples and 1710 legume samples from 19 Chinese provinces were pooled by type and province (giving 19 pooled cereal and 19 pooled legume samples). The SCCP and medium-chain chlorinated paraffin (MCCP) concentrations in the samples were determined by comprehensive two-dimensional gas chromatography tandem time-of-flight mass spectrometry (GC × GC-TOFMS). The mean SCCP concentrations in the cereal and legume samples were 343 and 328 ng g −1 wet weight (ww), respectively, and the mean MCCP concentrations were 213 and 184 ng g −1 ww, respectively. The dominant SCCP congener groups were C10 Cl6–7 in cereals and C10 Cl5–6 in legumes. The MCCP congener groups C14 Cl6–7 were dominant in both cereals and legumes. The CP concentrations were higher in samples from eastern China than in samples from other regions. Risk assessments indicated that SCCPs and MCCPs in cereals and legumes do not pose strong risks to Chinese residents. Highlights: SCCP and MCCP concentrations were determined in cereals and legumes from across China. The dominant SCCP congener groups were C10 Cl6–7 in cereals and C10 Cl5–6 in legumes. The dominant MCCP congener groups were C14 Cl6–7 in both cereals and legumes. The SCCP and MCCP concentrations were higher in East China than any other regions in China. The MCCPs may pose substantial health risks to residents in some provinces in China.